FILSAFAT MANUSIA: KONSEP, PERSPEKTIF DAN PENGARUH ILMU PENGETAHUAN TERHADAP TEKNOLOGI DAKWAH - Anggraini, Aulia; Syahfitri, Syahfitri (JURNAL DIALOKA: Jurnal Ilmiah Mahasiswa Dakwah dan Komunikasi Islam, 2022)
the purpose of this article is understand the importance of humans possessing knowledge and technology. A person with a lot of knowledge will know what to do and can solve problems that arise. Science is rapidly expanding and has an enormous impact on everyone's life. So scientific and technological advances are intertwined to make future life possible. Human knowledge and technology can change the perspective of ancient life and enrich the outlook of a better future. The findings suggest that human beings can possess knowledge and technology and that man enters an age of digital diversity. Philosophy and science are Bridges to changes and developments in the world of technology, so from the current technology's rise we are increasingly going from human power to sophisticated technological forces such as artificial intelligence and computers and from a technology we can get to science. It is thus inferred that a technology can actually give science